PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KARYAWAN BERPRESTASI MENGGUNAKAN METODE ADDITIVE RATIO ASSESSMENT (ARAS) STUDI KASUS : PT BINTANG MARAGA LINTAS MEDIA - Mochamad Adhari Adiguna, Khoeroni Firdaus (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
Employees are a vital element in supporting the operations of PT. Bintang Maraga Lintas Media, especially technicians who are directly involved in fieldwork. The company provides monthly bonuses to outstanding employees; however, the evaluation process remains subjective, relying solely on the supervisor's opinion based on attendance and overtime, without considering other aspects such as completed work orders, loyalty, responsibility, and discipline. To address this issue, this study aims to develop a Decision Support System (DSS) based on the Additive Ratio Assessment (ARAS) method to assist in evaluating employees objectively, measurably, and transparently. ARAS is chosen for its ability to perform multi-criteria evaluations logically, taking into account the weight and type of each criterion in a balanced manner. The results of this research show that the developed system can effectively manage employee assessment data and generate accurate rankings of outstanding employees, thereby supporting a fairer evaluation process and encouraging increased motivation and performance among employees.